Pertanggungjawaban Pidana Advokat pada Obstruction Of Justice Dalam Perkara Tindak Pidana Korupsi - Rahul Fauzan Saragih; Bakti Jaya Negara Pohan; Tetty Marlina Tarigan (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Law No 20 of 2001 concerning Eradication of Corruption which put the act of obstruction of justice becomes part of a corruption and can threaten the advocate profession in protecting the law interests of clients. Advocates have the immunity right during their duties and profession as regulated in Law Number 18 Year 2003 concerning Advocates. This study have aims to know the legal aspect of an advocate in law enforcement of obstruction of justice, also to find out the criminal responsibility of advocate in obstruction of justice that they do in the process of law enforcement for criminal action. This study using the normative method which namely the method used in legal research conducted by examining the literature and addressed to written regulations. This study showed that the immunity right can be applied as far as it's concerning to the criminal procedure that must be fulfilled by advocates both outside and inside the trial to protect the legal concerns of the client. Although the criminal liability of lawyers in obstruction of justice when it is proven to be harmful by conducting unlawful acts to obstruct the process of law enforcement of corruption, it possible to be held professionally and criminal liability. Keyword : Criminal responsibility, Advokat , Obstruction Of Justice